1981
DOI: 10.1002/1097-0142(19810501)47:9<2218::aid-cncr2820470918>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of dimethylhydrazine bowel carcinogenesis in rats

Abstract: An animal model of organ-specific chemical carcinogenesis has been used to study environmental effects on the incidence of human colorectal adenocarcinoma. Wistar/Furth weanling rats underwent connection of their urinary and fecal streams (ureterosigmoidostomy), connection of their urinary and fecal streams with proximal fecal diversion (rectal bladder), or sham operations. Age-matched, unoperated control and operated animals then received either no carcinogen, 1,2-dimethylhydrazine (DMH) 20 mg/kg body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Most authors consider that only one dose of 20 mg per kilogram of weight, injected weekly for 26 weeks, may induce a very high incidence of colorectal adenocarcinomas (18,19,(21)(22)(23)(24). However, even in these models a high incidence of tumors may be found, which rarely reaches 100% (25). Several modifications of these models were proposed in order to facilitate carcinogenesis, such as the addition of 5FU (26) or complex surgical modifications (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors consider that only one dose of 20 mg per kilogram of weight, injected weekly for 26 weeks, may induce a very high incidence of colorectal adenocarcinomas (18,19,(21)(22)(23)(24). However, even in these models a high incidence of tumors may be found, which rarely reaches 100% (25). Several modifications of these models were proposed in order to facilitate carcinogenesis, such as the addition of 5FU (26) or complex surgical modifications (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, even in these models a high incidence of tumors may be found, which rarely reaches 100% (25). Several modifications of these models were proposed in order to facilitate carcinogenesis, such as the addition of 5FU (26) or complex surgical modifications (25). In our model, we decided to use a 20-mg dose in subcutaneous injection plus the addition of a diet that was low in fiber but very high in fat and carbohydrates; based on recent studies over the anticarcinogenic action of calcium-rich diets (27), we used a diet poor in calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Pleomorphism, hyperchromasia, increased nucleus cytoplasm ratio and large nucleolus were the microscopic specifications of the malignant cells in this group. Other studies also confirmed this result indicating the colon tumour induction through injection or oral administration of DMH in 23-33 weeks [32][33][34] . Also, in shorter period (10 weeks) after DMH administration, preneoplastic lesions such as aberrant crypt foci (ACF) were observed 35 .…”
Section: Discussionmentioning
confidence: 57%
“…Another theory is the urine-stool admixture concept, which suggests that hydrolytic enzymes in the urine activate conjugated carcinogens in the stool. These carcinogens are most active at the junction of the two streams where the greatest concentration exists [ 5 , 10 , 11 ]. Other factors, such as chronic irritation of the bowel epithelium, instability of the borderline between the urothelium and colonic epithelium, metabolic changes, and the presence of a fresh colonic suture line may contribute to the induction of colon carcinoma after ureterosigmoidostomy [ 2 , 10 – 13 ].…”
Section: Case Presentationmentioning
confidence: 99%